2021
DOI: 10.1016/j.numecd.2021.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Low-density lipoprotein cholesterol levels are associated with poor clinical outcomes in COVID-19

Abstract: Background and Aims Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the sole causative agent of coronavirus infectious disease-19 (COVID-19). Methods and Results We performed a retrospective single-center study of consecutively admitted patients between March 1 st and May 15 th, 2020, with a definitive diagnosis of SARS-CoV-2 infection. The primary end-point was to evaluate the association of lipid ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…A systematic review and meta-analysis including 23 studies involving 10,122 COVID-19 patients showed that hospitalized patients with severe disease or non-survivor status had significantly lower serum LDL-C but not TG levels compared to patients with milder disease or survivor status; however, only a few studies of those with European ancestry were included [ 8 ]. A retrospective single-center study with 654 patients in Spain showed that LDL-C < 69 mg/dl at admission was independently associated with a greater risk of 30-day mortality from COVID-19 (hazard ratio, 1.94; 95% CI, 1.14–3.31, P = 0.014) [ 9 ]. However, a prospective single-center study with 48 COVID-19 patients in France did not detect a significant relationship between LDL-C and 28-day mortality [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review and meta-analysis including 23 studies involving 10,122 COVID-19 patients showed that hospitalized patients with severe disease or non-survivor status had significantly lower serum LDL-C but not TG levels compared to patients with milder disease or survivor status; however, only a few studies of those with European ancestry were included [ 8 ]. A retrospective single-center study with 654 patients in Spain showed that LDL-C < 69 mg/dl at admission was independently associated with a greater risk of 30-day mortality from COVID-19 (hazard ratio, 1.94; 95% CI, 1.14–3.31, P = 0.014) [ 9 ]. However, a prospective single-center study with 48 COVID-19 patients in France did not detect a significant relationship between LDL-C and 28-day mortality [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, serum lipid levels might be lower as a result of poor nutrition status due to COVID-19 severity [ 8 ]. Associations between serum lipid levels and COVID-19 risks might be secondary to immune-inflammatory responses that could worsen COVID-19 outcomes [ 8 , 9 , 11 ], though the association of LDL-C with COVID-19 mortality was independent of inflammatory markers in the above Spanish study [ 9 ]. MR studies can overcome such limitations of observational studies [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, LDL carries a large percentage of plasma Coenzyme Q10 (CoQ10), which has a significant antioxidant capacity and prevents peroxidative damage to cellular membranes [ 12 ]. Low LDL levels may contribute to endothelial dysfunction by causing a decrease in plasma CoQ10 levels.…”
Section: Sars-cov-2 and Cholesterolmentioning
confidence: 99%
“…Additionally, acute phase response during COVID-19 may lead to oxide-LDL formation and LDLR upregulation [ 12 ]. Oxide-LDL via lectin-like oxidized LDLR-1 (LOX-1) activation leads to ACE gene expression [ 33 ].…”
Section: Sars-cov-2 Angiotensin (Ang) II and Ldlr Mediated Plaque Formationmentioning
confidence: 99%
“…Some reports have shown that reduced levels of plasma total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C) may represent a laboratory signature of COVID-19 and that a progressive restoration of their preinfection levels may occur over COVID-19 clinical course up to recovery [ 7 , 8 ]. Moreover, reductions of TC, LDL-C, and HDL-C have been reported with increasing COVID-19 severity and uncontrolled inflammatory response [ 8 , 9 , 10 ], suggesting a possible bidirectional link between hypocholesterolemia and COVID-19 progression towards its worst clinical forms.…”
Section: Introductionmentioning
confidence: 99%